Pengaruh Kualitas Sistem Informasi, Kualitas Informasi, Dan Perceived Usefulness Terhadap Kepuasan Pengguna Akhir Software Akuntansi (Studi Empiris Pada Perusahaan Yang Menggunakan Sistem ERP) - Pamungkas, Fradela Aji; , Dra. Nursiam, M.H., Ak., CA (2017)
The study aims to analiyze the influence the information quality system, information quality, and perceived usefulness to the accounting software end-users satisfaction. Kind of this research is quantitative research. Data collection tehniques used by quesioner. In this study the samples were 68 employees of 8 companies that use ERP system. The sampling tehnique wan nonprobability sampling with purposive sampling. Data analysis methods used in this study was multiple linear regression analysis. The result of this research revelead that there was influence of information quality system, information quality, and perceived usefulness on the accounting software end-users satisfaction.